2008
DOI: 10.1007/bf03324748
|View full text |Cite
|
Sign up to set email alerts
|

Life course, gender and ethnic inequalities in functional disability in a Brazilian urban elderly population

Abstract: Decreasing social inequalities during childhood and adulthood will reduce socio-economic inequalities in disability in old age, especially among men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 53 publications
4
43
1
9
Order By: Relevance
“…This finding is consistent with the increased sensitivity described in validation studies, which has allowed for the use of the MMMSE and PFAQ in similar population studies (15,19) . Unlike other studies that observed higher rates of cognitive impairment in women (26,27) , neither the MMMSE nor the combination of the two screening measures showed a significant difference in cognitive decline by gender in the present study. The superior schooling of Chilean women, as well as their prolonged interactions with family members, might stimulate cognitive function (28,29) .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with the increased sensitivity described in validation studies, which has allowed for the use of the MMMSE and PFAQ in similar population studies (15,19) . Unlike other studies that observed higher rates of cognitive impairment in women (26,27) , neither the MMMSE nor the combination of the two screening measures showed a significant difference in cognitive decline by gender in the present study. The superior schooling of Chilean women, as well as their prolonged interactions with family members, might stimulate cognitive function (28,29) .…”
Section: Discussioncontrasting
confidence: 99%
“…These characteristics are common in the group of people with disabilities in ADLs. [19][20][21][22] The comparisons between the results with previous research are complicated due to the considerable differences in the study populations and the heterogeneity of the definitions of homebound status. 6 Not surprisingly, increasing age was significantly associated with being a homebound person, consistent with previous research conducted with older people.…”
Section: Discussionmentioning
confidence: 98%
“…[43][44][45][46][47][48][49][50][51][52][53][54][55][56] Guralnik et al 51 studied 1,122 elderly individuals and also found that the subjects with higher LLMS evaluated through FTSST presented greater functional independence, a conclusion that was obtained after four years of study. The study by Rosa et al 47 which investigated the determining factors of functional independence among elderly individuals, identified that females and individuals with advanced age presented greater probability of developing functional dependence (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%